Performance Characteristics of Electric Vehicle Battery using Charging Station System with Grid-Connected Configuration via Matlab Simulation - Tan, Chong Chiat; Mohamad, Khairul Anuar; Alias, Afishah; Mohd Sanip, Mohd Shafiee; Abdullah, Norisham; Nordin, Mohammad Syahmi (Journal of Electronic Voltage and Application, 2021)
Due to the increase in demand for electric vehicles (EV) in recent years, the lack of EV charging stations and different EVs’ battery types are causing inconvenience to the user. The paper presents modeling and simulation of the grid-connected EV charging station system using MATLAB Simulink platform. The model consists of LCL filter, inverter, and battery charger. The inverter is regulated by a dq-frame that synchronizes with a phase-locked loop (PLL) to convert a three-phase alternating current (AC) source to a direct current (DC) source. Futhermore, lead acid (Pb-acid), lithium-ion (Li-ion), nickel-cadmium (Ni-Cd), and nickel metal hydride (Ni-MH) were tested and their performances were evaluated using the simulated EV charging station. All simulations were carried out and tested in the MATLAB Simulink platform. The results showed that Li-ion battery reaches the highest state-of-charge (SOC) value which is 51.66%, Pb-acid is 51.60%. Ni-MH is 51.55%, and Ni-Cd is 51.47% within 60s. The voltage values are 226.0V, 225.2V, 220.8V, and 220.2V for Pb-acid, Ni-MH, Ni-Cd and Li-ion, respectively. The findings revealed that the lithium ion is the most suitable for the use of EV since it had the fastest charging and slowest to reach its maximum threshold value of charging voltage.